Rapid Nanoparticle Synthesis by Magnetic and Microwave Heating - Chikan, Viktor; McLaurin, Emily J. (My University, 2016)
Traditional hot-injection (HI) syntheses of colloidal nanoparticles (NPs) allows good separation of the nucleation and growth stages of the reaction, a key limitation in obtaining monodisperse NPs, but with limited scalability. Here, two methods are presented for obtaining NPs via rapid heating: magnetic and microwave-assisted. Both of these techniques provide improved engineering control over the separation of nucleation and growth stages of nanomaterial synthesis when the reaction is initiated from room temperature. The advantages of these techniques with preliminary data are presented in this prospective article. It is shown here that microwave assisted heating could possibly provide some selectivity in activating the nanomaterial precursor materials, while magnetic heating can produce very tiny particles in a very short time (even on the millisecond timescale), which is important for scalability. The fast magnetic heating also allows for synthesizing larger particles with improved size distribution, therefore impacting, not only the quantity, but the quality of the nanomaterials.
Citation: Chikan, V., & McLaurin, E. J. (2016). Rapid Nanoparticle Synthesis by Magnetic and Microwave Heating. Nanomaterials, 6(5), 9. doi:10.3390/nano6050085
Keywords: Nanoparticle Synthesis; Quantum Dot Synthesis; Nanocrystal Quantum Dots; Assisted Synthesis; Solar-Cells; Chemistry